Steady-state force-velocity relation in the ATP-dependent sliding movement of myosin-coated beads on actin cables in vitro studied with a centrifuge microscope. - Oiwa, K (1990)
To eliminate the gap between the biochemistry of actomyosin in solution and the physiology of contracting muscle, we developed an in vitro force-movement assay system in which the steady-state force-velocity relation in the actin-myosin interaction can be studied. The assay system consists of the internodal cells of an alga, Nitellopsis obtusa, containing well-organized actin filament arrays (actin cables); tosyl-activated polystyrene beads (diameter, 2.8 microns; specific gravity, 1.3) coated with skeletal muscle myosin; and a centrifuge microscope equipped with a stroboscopic light source and a video system. The internodal cell preparation was mounted on the rotor of the centrifuge microscope, so that centrifugal forces were applied to the myosin-coated beads moving along the actin cables in the presence of ATP. Under constant centrifugal forces directed opposite to the bead movement ("positive" loads), the beads continued to move with constant velocities, which decreased with increasing centrifugal forces. The steady-state force-velocity curve thus obtained was analogous to the double-hyperbolic force-velocity curve of single muscle fibers. The unloaded velocity of bead movement was 1.6-3.6 microns/s (20-23 degrees C), while the maximum "isometric" force generated by the myosin molecules on the bead was 1.9-39 pN. If, on the other hand, the beads were subjected to constant centrifugal forces in the direction of bead movement ("negative" loads), the bead also moved with constant velocities. Unexpectedly, the velocity of bead movement did not increase with increasing negative loads but first decreased by 20-60% and then increased towards the initial unloaded velocity until the beads were eventually detached from the actin cables.